Rapid and sensitive determination of bongkrekic acid with molecularly imprinted polymer-coated wooden-tip electrospray ionization mass spectrometry - Chunfei Zhong; Xinyan Li; Fan Zhang; Ning Liu; Jiewei Deng; Yunyun Yang; Tiangang Luan (Advances in Sample Preparation)
In this study, a novel methodology has been developed for the rapid and sensitive analysis of bongkrekic acid (BA), a highly toxic bacterial metabolite, using a molecularly imprinted polymer-coated wooden-tip coupled with electrospray ionization mass spectrometry (MIPWT-ESI-MS). A MIPWT solid phase microextraction (SPME) probe specifically tailored for BA was fabricated, by employing dummy template molecules/functional monomers in the imprinting coating modification. This approach exhibits an enrichment factor (EF) of 683 ± 53 for efficient extraction of BA from aqueous matrices, demonstrating the utility of dummy templates in enhancing the selectivity and sensitivity of the MIPWT-ESI-MS method. The analytical performance of the MIPWT-ESI-MS method was evaluated, demonstrating a desirable linear correlation (r = 0.9988), along with remarkable sensitivity by a limit of detection (LOD) and limit of quantitation (LOQ) at 0.05 μg/L and 0.16 μg/L in pure water, respectively. Additionally, the method demonstrated high repeatability with a relative standard deviation (RSD) < 3.9 % (n = 6) and reproducibility with an RSD < 13.4 %. The practical application of the method was confirmed through the successful analysis of real-world samples, including tap water, wastewater from a food processing factory, and the aqueous extracts of food samples, with BA detected at 0.296 µg/L in Tremella. Spiking experiments further validated the accuracy of the method, with recoveries ranging from 81 % to 97 %. This study integrates MIP with ambient mass spectrometry, offering a robust, selective, and sensitive tool for the monitoring of trace BA levels in complex food and environmental samples, contributing significantly to public health safety and food quality control.